2020
DOI: 10.1128/mbio.00919-20
|View full text |Cite
|
Sign up to set email alerts
|

The Arginine Deiminase Pathway Impacts Antibiotic Tolerance during Biofilm-Mediated Streptococcus pyogenes Infections

Abstract: ABSTRACT Bacterial biofilms are responsible for a variety of serious human infections and are notoriously difficult to treat due to their recalcitrance to antibiotics. Further work is necessary to elicit a full understanding of the mechanism of this antibiotic tolerance. The arginine deiminase (ADI) pathway is responsible for bacterial pH maintenance and is highly expressed during biofilm growth in multiple bacterial species. Using the group A Streptococcus Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…Collectively, the arc genes convert arginine into ornithine, ammonia, and carbon dioxide, yielding 1 mol of ATP per mol of arginine. Indeed, our data showed strong up regulation of the arcABDCR operon in 24-h biofilms of UAS391 and HEMRSA-15, and in 48-h biofilms of ST239-16, and a critical role of arginine deiminase ArcA, where inactivation led to a distinct decrease in biofilm formation by USA300-JE2 at 24 h. The contribution of ArcA and the ADI pathway has previously been reported in Staphylococcus epidermidis (Lindgren et al, 2014) and, recently, Streptococcus pyogenes (Freiberg et al, 2020). Moreover, we also found a second ADI pathway-encoded gene, carbamate kinase (ArcC), which transfers phosphate from carbamoyl phosphate to ADP, to be a key regulator of biofilm formation.…”
Section: Discussionsupporting
confidence: 76%
“…Collectively, the arc genes convert arginine into ornithine, ammonia, and carbon dioxide, yielding 1 mol of ATP per mol of arginine. Indeed, our data showed strong up regulation of the arcABDCR operon in 24-h biofilms of UAS391 and HEMRSA-15, and in 48-h biofilms of ST239-16, and a critical role of arginine deiminase ArcA, where inactivation led to a distinct decrease in biofilm formation by USA300-JE2 at 24 h. The contribution of ArcA and the ADI pathway has previously been reported in Staphylococcus epidermidis (Lindgren et al, 2014) and, recently, Streptococcus pyogenes (Freiberg et al, 2020). Moreover, we also found a second ADI pathway-encoded gene, carbamate kinase (ArcC), which transfers phosphate from carbamoyl phosphate to ADP, to be a key regulator of biofilm formation.…”
Section: Discussionsupporting
confidence: 76%
“…The precise molecular mechanisms that underpin how this system renders the bacterial cell resistant to Zn intoxication requires further definition but arginine deaminase typically converts arginine to ammonia, ATP and ornithine; overproduction of one of these may support bacterial survival during Zn stress. A recent study identified arginine deaminase as a key factor in resistance to antibiotics and biofilm formation in S. pyogenes (42). Numerous prior studies have reported elevated expression of arc genes in S. agalactiae in response to acid stress (43), human serum (44), blood (45), or amniotic fluid (46).…”
Section: Discussionmentioning
confidence: 99%
“…Several upregulated genes of flagellins (BPSL0268, and BPSL3319), type III secretion system (e.g., BPSS1524, BPSS1525, BPSS1529, BPSS1531, BPSS1532, BPSS1533, BPSS1543, and BPSS1545), chemotaxis (e.g., BPSL3300 and BPSL3301, BPSL3303, BPSL3305, and BPSL3299), included LuxR family transcriptional regulator and two-component system (e.g., BPSS0312 and BPSS1522) were responsible for the regulation of bacteria-associated surface and bacterial virulence factors. , The expression of stress related proteins such as heat shock protein hslU and hslV (e.g., BPSL0203 and BPSL0204) and chaperone protein (e.g., BPSL2826 and BPSL3080) were also shown more up-regulated in biofilm (e.g., BPSL0203, BPSL0204, and BPSL3080), suggesting bacterial adaptation to biofilm-related stress . The metabolism of gene-related amino acid such as arginine linked to energy metabolism and resisting to acid stress (e.g., BPSL0926 and BPSL1742) was necessary to generate energy via urea-cycle and bacterial pH maintenance in bacterial biofilm . The upregulation of gene-related phenyl acetate (PA) degradation (e.g., BPSL0059, BPSL3041, BPSL3042, and BPSL3234) involved bacteria aerobic hybrid pathway to degrade PA as a sole carbon source for energy consumption .…”
Section: Resultsmentioning
confidence: 99%